Acceptability and benefit of rectal irrigation in patients with low anterior resection syndrome: a qualitative study. (1st March 2018) - McCutchan, G. M.; Hughes, D.; Davies, Z.; Torkington, J.; Morris, C.; Cornish, J. A.; ,
Abstract: Aim: Low anterior resection syndrome (LARS) following rectal cancer surgery impairs the patient's quality of life (QoL). Rectal irrigation has been demonstrated to be effective for anterior resection syndrome but many surgeons do not suggest it as a treatment. This feasibility study aimed to explore treatment acceptability and the benefit of rectal irrigation in patients who developed LARS following an anterior resection for rectal cancer. Method: This was a qualitative study involving semi‐structured interviews. Twenty‐one patients diagnosed with LARS following anterior resection for rectal cancer in a single tertiary centre were offered rectal irrigation as a treatment option. Qualitative interviews ( n = 17) were conducted at baseline to explore the patient‐reported impact of LARS on QoL, treatment acceptability and factors influencing the decision to accept/decline treatment. Follow‐up interviews were carried out at 6 months for the treatment group only ( n = 12), to assess its practicality and impact on QoL. Results: Qualitative interview findings suggest that rectal irrigation is an acceptable method of treatment for LARS. Participants who perceived their symptoms to be more severe or poorly controlled were most likely to consider rectal irrigation as a treatment option. Patients who completed treatment reported improvements in their QoL, the ability to control the time of defaecation being the key benefit. Conclusion: Clinicians should consider offering rectal irrigation as a treatment option to patients presenting with bowel dysfunction following anterior resection as it can improve symptoms. Patients who perceive that their symptoms are severe are more likely to consider treatment.